Loss and Damage - COP29 Updates - Jeanneau, Louise (2024)
Loss and Damage (L&D) refers to the unavoidable impacts of climate change that exceed what communities can adapt to. These impacts include economic losses like damaged infrastructure and disrupted livelihoods, as well as non-economic losses, such as the loss of cultural heritage and biodiversity (UNFCCC, UNEP). L&D is a matter of climate justice and in this way, is closely related to the concept of Just Transition, as the most vulnerable countries to the adverse effects of climate change are often the lowest emitters of greenhouse gases.